Radial Head Prosthetic Replacement in Adolescents: A Report of 5 Cases. Issue 2 (6th December 2021) - Rotman, Dani; Rojas Lievano, Jorge; Kwak, Jae-Man; O'Driscoll, Shawn W.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The management of severe radiocapitellar joint pathologies in young patients is challenging. Radial head arthroplasty (RHA) is a treatment option in the adult population, but most surgeons avoid implementing it in younger patients, and there are no published results for patients younger than 16 years. Methods: Our retrospective cohort describes 5 patients (4 male 1 female) who underwent cementless modular RHA at an average age of 14 years (range: 13 to 15). The preoperative diagnoses were post-traumatic radiocapitellar incongruity and arthrosis because of previous Salter-Harris type 3 or 4 fractures of the radial head in 3 cases; and axial instability of the forearm following failed radial head excision in 2 cases. Because of the complexity of the elbow pathology in these cases, all underwent concomitant procedures including: contracture release (5 cases), corrective ulnar osteotomy (2 cases), distal ulnar shortening osteotomy, excision of radioulnar synostosis, microfracture of the capitellum, and partial excision of the medial triceps (1 case each). Collected data included patient-reported outcomes, visual analog scale pain score at rest and during physical activity and radiographic assessment of arthritis and prosthesis loosening. Results: Average clinical follow-up was 8 years (range: 3 to 13). All 5 patients were pain-free at rest, and 3 reported moderate elbow pain (visual analog scale: 5 to 6) with physical activity. At an average radiographic follow-up of 3 years (range: 0.5 to 5), 3 patients showed mild progression of elbow arthrosis, but there were no signs of progressive capitellar erosion or implant loosening. Only 1 complication was noted—development of heterotopic ossification in 1 patient, which required open heterotopic ossification excision and contracture release 2 years following the RHA. None of the patients required prosthesis revision or removal. Conclusion: RHA was successful in improving pain and axial forearm stability in this very small series of adolescent patients. Concerns regarding long-term longevity and complications still exist. Considering the lack of other reliable treatment options, RHA may be indicated in this challenging patient population. Level of Evidence: Level IV: therapeutic study—case series.